2015
DOI: 10.1007/s13277-015-4290-5
|View full text |Cite
|
Sign up to set email alerts
|

HNF1β drives glutathione (GSH) synthesis underlying intrinsic carboplatin resistance of ovarian clear cell carcinoma (OCCC)

Abstract: Chemoresistance to platinum-based antineoplastic agents is a consistent feature among ovarian carcinomas; however, whereas high-grade serous carcinoma (OSC) acquires resistance during chemotherapy, ovarian clear cell carcinoma (OCCC) is intrinsically resistant. The main objective of this study was to explore, in vitro and in vivo, if hepatocyte nuclear factor 1β (HNF1β) and glutaminolysis contribute for the resistance of OCCC to carboplatin through the intrinsically increased GSH bioavailability. To disclose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…HNF-1β may repair damage caused by oxidative stress and can promote survival by upregulating antioxidant proteins via binding with antioxidant response element (37,68,81,83,84). This gene upregulates the synthesis of glutathione (GSH), a powerful antioxidant (85). HNF-1β also triggers ROS resistance in CCC cells via rBAT, a cystine transporter (68).…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
“…HNF-1β may repair damage caused by oxidative stress and can promote survival by upregulating antioxidant proteins via binding with antioxidant response element (37,68,81,83,84). This gene upregulates the synthesis of glutathione (GSH), a powerful antioxidant (85). HNF-1β also triggers ROS resistance in CCC cells via rBAT, a cystine transporter (68).…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
“…EAOC allows the rapid reduction of metHb possibly through the conversion of metHb into oxyHb (in vivo autoreduction). Glutathione, an antioxidant overexpressed in EAOC, is shown to be responsible for the conversion of metHb to oxyHb (14,15). The difference in the metHb-to-oxyHb ratio between benign and malignant endometriosis supports the hypothesis that this is not a consequence of the simple dilution of the cyst fluids.…”
Section: Modern Approaches To Noninvasive Diagnosis Of Malignant Tranmentioning
confidence: 62%
“…The platinum drugs induce cell death through two mechanisms: the establishment of adducts of DNA and proteins, and the generation of reactive oxygen species (ROS) [9,10]. We have previously found that ovarian cancer cells exhibit a great metabolic reliance on cysteine and glutathione (GSH), as these thiols were shown to protect cells under stressful conditions such as hypoxia or carboplatin exposure, hence, also accounting for chemoresistance [11][12][13]. GSH can explain this protective effect given its role as a ROS scavenger and as a pivotal drug detoxifier, allowing cells to evade cell death [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…GSH can explain this protective effect given its role as a ROS scavenger and as a pivotal drug detoxifier, allowing cells to evade cell death [14][15][16][17][18]. We have reported that chemoresistance, supported by high GSH levels, can be abrogated upon the exposure to l-buthionine sulfoximine (l-BSO) [11], an inhibitor of γ-glutamylcysteine ligase (GCL), the first enzyme catalyzing the synthesis of GSH [19,20]. However, the systemic administration of l-BSO is associated to an elevated toxicity, since l-BSO is an irreversible inhibitor of GCL [19].…”
Section: Introductionmentioning
confidence: 99%